(untitled) (PENDAIS, 2021)
This study aims to elaborate and reveal how important character education is in the family environment. The method used in this research is qualitative using a literature-based approach, namely looking for references through articles and other sources that are considered relevant and representative. The results of the study and discussion show that character education has existed since the pre-independence era, but it is not termed that way but character education, morals, and Pancasila. The term character education became popular since 2010 in the post-reform period; Character education in the pre-national policy period of character building has not been fully framed in the National education system. The context of character education in national education is still implicit in education based on culture, Pancasila and religion. The organizers have not yet been comprehensively regulated. Meanwhile, after the national policy of character building, character education has become a hallmark of the national education system, and its implementation is regulated in detail starting from the implementation strategy to the evaluation stage.